2017
DOI: 10.1089/neu.2015.4340
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury Causes Endothelial Dysfunction in the Systemic Microcirculation through Arginase-1–Dependent Uncoupling of Endothelial Nitric Oxide Synthase

Abstract: Endothelial dysfunction is a hallmark of many chronic diseases, including diabetes and long-term hypertension. We show that acute traumatic brain injury (TBI) leads to endothelial dysfunction in rat mesenteric arteries. Endothelial-dependent dilation was greatly diminished 24 h after TBI because of impaired nitric oxide (NO) production. The activity of arginase, which competes with endothelial NO synthase (eNOS) for the common substrate l-arginine, were also significantly increased in arteries, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 61 publications
(82 reference statements)
4
58
3
Order By: Relevance
“…However, it was later shown that endothelial dysfunction of peripheral vessels plays the leading role in the generalization of oxidative stress during cerebral ischaemia [6]. Key enzymes have been identified that are responsible for the production of ROS (cyclooxigenase-2, arginase and endothelial NO synthase) [6][7][8]. Despite the fact that thiols are part of the antioxidant system, as noted above, their oxidation products are cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was later shown that endothelial dysfunction of peripheral vessels plays the leading role in the generalization of oxidative stress during cerebral ischaemia [6]. Key enzymes have been identified that are responsible for the production of ROS (cyclooxigenase-2, arginase and endothelial NO synthase) [6][7][8]. Despite the fact that thiols are part of the antioxidant system, as noted above, their oxidation products are cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, acute ischaemic injury causes systemic oxidative stress, which is associated with inflammatory responses in peripheral arteries [3,6]. As a result, blood plasma vasoconstrictor activity is elevated because of the massive release of reactive oxygen species (ROS) and cytokines [5,7,8]. It has been suggested that this contributes to a hypertensive state and has negative effects on the course and outcome of stroke [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There is both immediate (due to tissue damage and acute inflammation) and delayed (mainly result of chronic inflammation) disruption of BBB during TBI. Endothelial dysfunction because of acute inflammation contributes to systemic complications after head injury (Villalba et al., ). The disruption of tight junctions and basement membrane causes increased paracellular permeability (Komarova & Malik, ; Mehta & Malik, ).…”
Section: Endothelial Cells/bbbmentioning
confidence: 99%
“…Such microvascular endophenotype was well recapitulated in animal models of TBI [6], with completely different injury settings including fluid percussion injury, controlled cortical impact and blast injury. Mechanistically, TBI induces endothelial dysfunction [19], disrupts the crosstalk between endothelial cells and pericytes [20], reduces cerebral blood flow (CBF) and causes tissue hypoxia [21], upregulation of vascular endothelial growth factor (VEGF) and metallopeptidases [22,23], leukocyte infiltration [24], gliosis and neuroinflammation [7], which all contribute to BBB dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Such microvascular endophenotype was well recapitulated in animal models of TBI [6], with completely different injury settings including fluid percussion injury, controlled cortical impact and blast injury. Mechanistically, TBI induces endothelial dysfunction [19], disrupts the crosstalk between endothelial cells and pericytes [20], reduces cerebral blood flow (CBF) and causes tissue hypoxia [21], upregulation of vascular endothelial growth factor (VEGF) and metallopeptidases [22,23], leukocyte infiltration [24], gliosis and neuroinflammation [7], which all contribute to BBB dysfunctions.As the interface between the circulation and central nervous system (CNS), the BBB plays a key role in normal brain physiological regulation and homeostasis [25]. Anatomically, it consists of continuous endothelia sealed by highly specialized intercellular junctional structures to restrict paracellular flow, and highly selective transport systems eliminating toxic substances yet allowing exchanges of nutrients and metabolites between circulation and brain [11,25].…”
mentioning
confidence: 99%